PERAMALAN PRODUKSI JAMBU MENTE DI DAERAH ISTIMEWA YOGYAKARTA BERDASARKAN LUAS AREAL TANAM TAHUN SEBELUMNYA - Saras Winarbawa (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1999)
Estimation of cashewnut production in Yogyakarta Special District was very important in coming period, as well as with cost planning, income and marketing. This paper proposed one mathematical estimation method for estimating of cashewnut production in Yogyakarta Special District. The result shows that cashewnut production in that district would be 0.62 percent increasing every year on 1996-2001 period. Cashewnut production on 2001 was estimated to reach 315.62 ton. The correlation between estimating production (Y) with year to-t (X) on 1996-2001 had equation: Ln Y = 5.7055 + 0.0196 Ln X (r=0.74) Key word: Anacardium accidentale, L., planning area vast, productivity.